Knowledge and practice of breast self-examination among women of reproductive age in Budiganga community of Morang, Nepal - sharma, Ismita; Anjali Mishra,; Ayushma Shakya,; Shivraj Sharma, (Asian Journal of Medical Sciences, 2025)
Background: Breast cancer is one of the leading causes of illness and death among women worldwide. Early detection through breast self-examination (BSE) plays a crucial role in improving survival rates. However, in many low-resource settings, both awareness and practice of BSE remain limited. Aims and Objectives: The aim of this study was to assess the level of knowledge and practice of BSE among reproductive-age women in the Budhiganga community of Morang, and to examine the association between sociodemographic factors and BSE knowledge and practice. Materials and Methods: A descriptive cross-sectional study was conducted, with data collected from a representative sample of reproductive-age women using a structured questionnaire. Participants were selected through random sampling, and the data were analyzed using descriptive statistics to evaluate the level of knowledge and frequency of BSE practice. Results: The study revealed that 72.4% of participants had heard of BSE, but only 5.4% reported practicing it regularly. While the majority recognized that BSE should be performed monthly (94%) and started in their 20s (96.7%), selected sociodemographic variable age ,marital status, education. occupation and monthly income was not found associated with knowledge and practice of BSE. Conclusions: The findings underscore the need for targeted community-based health education programs to enhance both knowledge and the practice of BSE. Raising awareness and providing hands-on training can help improve early breast cancer detection and contribute to reducing the disease burden in resource-limited communities.